2021
DOI: 10.1200/go.21.00209
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Pathologic Diagnosis in Patients With Lymphoma and Survival: A Prospective Analysis From Botswana

Abstract: PURPOSE With intense HIV epidemics, southern African countries have a high burden of classic Hodgkin lymphoma (CHL) and non-Hodgkin lymphoma (NHL). However, suboptimal access to pathology resources limits subtype classification. We sought to assess the diagnostic accuracy of specimens classified as lymphoma and to determine association between discordant pathologic diagnosis and overall survival. METHODS Seventy patients with CHL or NHL and treated at three Botswana hospitals from 2010 to 2016 were analyzed. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…We also cannot exclude the possibility that our results could have been confounded by misdiagnoses, as external pathology review of HL and NHL cases in Botswana suggest. 26,27 In conclusion, in this cohort receiving longstanding ART, patients with HL living with HIV experienced comparable survival to their HIV-uninfected counterparts. Molecular genetic studies comparing HL cases are indicated to explore whether differences in HIV HL may confer a clinical benefit.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…We also cannot exclude the possibility that our results could have been confounded by misdiagnoses, as external pathology review of HL and NHL cases in Botswana suggest. 26,27 In conclusion, in this cohort receiving longstanding ART, patients with HL living with HIV experienced comparable survival to their HIV-uninfected counterparts. Molecular genetic studies comparing HL cases are indicated to explore whether differences in HIV HL may confer a clinical benefit.…”
Section: Discussionmentioning
confidence: 69%
“…We also cannot exclude the possibility that our results could have been confounded by misdiagnoses, as external pathology review of HL and NHL cases in Botswana suggest. 26,27…”
Section: Discussionmentioning
confidence: 99%
“…We believe detailed diagnostic and therapeutic guidelines for pediatric DL cases would reduce the time to establish a diagnosis and, therefore, reduce the time taken to administer effective treatment for the patient. Establishing standardised treatment guidelines for pediatric lymphoma patients is especially important since according to recent literature, a discordant diagnosis was found to be associated with an approximate three-fold increased risk of death [ 12 ].…”
Section: Discussionmentioning
confidence: 99%